PENERAPAN MODEL PEMBELAJARAN LANGSUNG (THE APPLICATION OF DIRECT INSTRUCTIONAL MODEL) UNTUK MENINGKATKAN KEMAMPUAN MENGGAMBAR EKSPRESI PADA SISWA KELAS II SDN 177 PEKANBARU - Grissilda, Rica; Antosa, Zariul; Alim, Jesi Alexander (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractDirect Instruction is a model or approach to teaching that is designed to supportthe teaching and learning process with the pattern of activity gradually or step bystep . The purpose of this research is to improve the ability to draw artistic andcultural expression in learning and skills . Subject students / 177 ElementarySchool second graders Pekanbaru . Based on data analysis , shows the averageactivity of the teacher at the first meeting of 1 cycle at 45 with less categories ,improved in the 2nd meeting of the first cycle to 60 . And the second cycle 1meeting increased to 75 later in the meeting to a 2 second cycle increased to 90with the excellent category . Average activity of students in the first cycle was 55the first meeting with Simply categories , increased in the first 2 cycles meeting is60 . In the second cycle of 1 to 80 with a meeting of either category , then on the2nd meeting of the second cycle increased to 90 with the excellent category .From the results of the activities of teachers and students showed improvement .From the expressions drawing skills assessment results indicate the average valuewas 56.44 in the preliminary data on the assessment of the ability to drawexpressions in the first cycle increased by 14,78 points with an average of 71.22from the initial data . In the assessment of image expression cycles both students 'average score increased to 81.67 and 10.45 the expression increased withdrawing cycle assessment results I. This shows that the application of directinstructional model can improve student 's ability to draw class II expression SDN177 Pekanbaru .